Role of CD44 as a marker of cancer stem cells in head and neck cancer - Trapasso, Serena (Dove Medical Press, 2012)
In recent years, many studies have shown that some types of tumors are characterized by the presence of cells with stem-like characteristics, called cancer stem cells (CSCs). These are considered cells that initiate the tumor and are probably responsible for tumor recurrence. CSCs have the capacity for self-renewal, the potential to give rise to one or more cell types within the tumor, and the ability to drive, in a continuous manner, the proliferation of malignant cells. The failure of current cancer therapies can be attributed to the relative ineffectiveness of drugs against CSCs, which remain viable while retaining their full ability to reproduce the tumor. The development of new strategies is currently hampered by the lack of reliable markers to identify CSCs. One promising surface marker of CSCs in head and neck cancer is the CD44 molecule, which has been shown in preliminary studies to have high specificity, although there are discrepant data because its prognostic value may depend on the specific tumor location. More rigorous studies are needed to investigate the usefulness of CD44 expression in head and neck tumors for possible clinical applicability.